Research progress on related mechanisms of uric acid activating NLRP3 inflammasome in chronic kidney disease. Issue 1 (31st December 2022) - Wang, Miao; Lin, Xin; Yang, Xiaoming; Yang, Yanlang
Abstract: Hyperuricemia is an independent risk factor for the progression of chronic kidney disease. High levels of uric acid can lead to a series of pathological conditions, such as gout, urinary stones, inflammation, and uric acid nephropathy. There is a close relationship between uric acid and the NLRP3 inflammasome. NLRP3 inflammasome activation can cause cell damage and even death through endoplasmic reticulum stress, lysosome destruction, mitochondrial dysfunction, and the interaction between the Golgi apparatus and extracellular vesicles. In addition, the NLRP3 inflammasome acts as a molecular platform, triggering the activation of caspase-1 and the lysis of IL-1β, IL-18 and Gasdermin D (GSDMD) through different molecular mechanisms. Cleaved NT-GSDMD forms pores in the cell membrane and triggers pyrophosphorylation, thereby inducing cell death and releasing many intracellular proinflammatory molecules. In recent years, studies have found that hyperuricemia or uric acid crystals can activate NLRP3 inflammasomes, and the activation of NLRP3 inflammasomes plays an important role in kidney disease. This article reviews the possible pathophysiological mechanisms by which uric acid activates inflammasomes and induces kidney damage at the cellular and molecular levels.